Morning Day Culture dalam Menguatkan Prestasi Belajar Siswa SMKN 1 Palangka Raya - Norrahmah Hidayatul Janah; Noorazmah Hidayati; Muhammad Redha Anshari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Encouraging learning environments and strong teacher-student interactions are prerequisites for effective learning. Learning achievement can be enhanced by classroom environments that foster positive interactions between teachers and students, but it can also be impacted by school culture, one aspect of which is the morning culture. The aim of this research is to ascertain how the adoption of a morning-day culture will enhance students' academic performance. This research employs a case study methodology combined with a qualitative approach. The grade XI pupils and the instructor in charge of the morning day culture program are the subjects of this investigation. The class XI homeroom teacher served as the research informant. The methods of gathering data include documentation, interviews, and observation. Triangulating sources and approaches is one of the techniques used for data validation. Techniques for data analysis include gathering, reducing, presenting, and verifying data or drawing conclusions. The study's findings demonstrate that the morning day culture program at SMKN 1 Palangka Raya is implemented in a different way each day. Specifically, the flag ceremony is held on Monday, socialization or habituation is done on Tuesday, literacy is done on Wednesday, the school environment is cleaned on Thursday, and group gymnastics is done on Friday morning. In addition to serving as a routine, the morning day culture program has a big impact on the students at SMKN 1 Palangka Raya. For example, students in good physical and mental health find it easier to focus during class; students who are happy and motivated at school are more engaged in their studies; and literacy and socialization activities help students develop their critical thinking and problem-solving skills. As a result, by enhancing character, enhancing health, and fostering skill development, this morning culture supports student learning achievement